2016
DOI: 10.1016/j.enconman.2016.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Influences of bipolar plate channel blockages on PEM fuel cell performances

Abstract: In this paper, the effect of partial-or full-block placement along the flow channels 15 of PEM fuel cells is numerically studied. Blockage in the channel of flow-field diverts the flow into the 16 gas diffusion layer (GDL) and enhances the mass transport from the channel core part to the catalyst 17 layer, which in turn improves the cell performance. By partial blockage, only a part of the channel flow 18 is shut off. While in full blockage, in which the flow channel cross sections are fully blocked, the only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(62 citation statements)
references
References 28 publications
1
61
0
Order By: Relevance
“…This research was conducted by numerical simulation using Ansys Fluent software. The model used is a single stack PEM fuel cell consisting of 9 layers, there are: a MATEC Web of Conferences 197, 08010 2018https://doi.org/10.1051/matecconf/201819708010 AASEC 2018 pair of current collectors, a pair of reactant fluids, a pair of diffusion layer gases, a pair of catalyst layers, and a membrane [18]. The active membrane area used is 14 cm 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research was conducted by numerical simulation using Ansys Fluent software. The model used is a single stack PEM fuel cell consisting of 9 layers, there are: a MATEC Web of Conferences 197, 08010 2018https://doi.org/10.1051/matecconf/201819708010 AASEC 2018 pair of current collectors, a pair of reactant fluids, a pair of diffusion layer gases, a pair of catalyst layers, and a membrane [18]. The active membrane area used is 14 cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…where φ is transport quantity, ρ is mixture density, V is velocity, Γ is diffusivity, and S is source term. Driving force electrochemical reactions that occur is a potential in solid phase and phase membrane [18]:…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al [22] approved numerically that, the smaller channel size improves the cell performance by enhancing the species transport toward the porous layer through the promoting of the under-rib convection. Heidary et al [24], Ghanbarian et al [25] and Tiss et al [26] studied the impact of the flow channel blockage on the PEM fuel cell performance. Their results revealed that, the higher blockage of the flow channel led to more under-rib convection species transport, more uniform distribution over the catalyst layer, and in turn higher cell performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, excess water present in the cell may block the available paths for oxygen diffusion and limits the reaction rate in catalyst layers (CLs), drastically reducing the cell performance , . This phenomenon is termed “flooding” and has been a major factor that restricts the cell performance , .…”
Section: Introductionmentioning
confidence: 99%